Volume 5A: Heat Transfer 2016
DOI: 10.1115/gt2016-57579
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Injection Effect on a Transonic Squealer Tip: Part 1 — Experimental Heat Transfer Results and CFD Validation

Abstract: Recent studies have demonstrated that the aerothermal characteristics of turbine rotor blade tip under a transonic condition are qualitatively different from those under a low speed subsonic condition. The cooling injection adds further complexity to the Over-Tip-Leakage (OTL) transonic flow behavior and aerothermal performance, particularly for commonly studied shroudless tip configurations such as a squealer tip. However there has been no published experimental study of a cooled transonic squealer. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…With the computational setup mentioned above, satisfactory agreements between experimental and CFD results have been reported by previous tip studies by Ma et al [25,26]. Further validations of the CFD performance on tip heat transfer at the high speed (exit Mach number 0.86) and a low speed condition (exit Mach number 0.45) are presented in Fig.…”
Section: Numerical Setup and Validationsupporting
confidence: 76%
See 1 more Smart Citation
“…With the computational setup mentioned above, satisfactory agreements between experimental and CFD results have been reported by previous tip studies by Ma et al [25,26]. Further validations of the CFD performance on tip heat transfer at the high speed (exit Mach number 0.86) and a low speed condition (exit Mach number 0.45) are presented in Fig.…”
Section: Numerical Setup and Validationsupporting
confidence: 76%
“…The experimental tip HTC contour shown in Fig 3a was produced with the same experimental data by Ma et al [24] in a high speed condition. The experimental methods and uncertainty analysis were detailed by Ma et al [24] and Ma et al [25]. The overall trend and local variations are very different between high speed flow ( Fig.…”
Section: Numerical Setup and Validationmentioning
confidence: 99%
“…It has a better performance when predicting HTC on blade tip surface than the Spalart-Allmaras (SA) model, as is validated by Ma et al. 19 The result from the SST model shows better accordance with the experimental result. The computation domain is a single passage domain with periodic boundaries on both sides.…”
Section: Cfd Methods and Setupmentioning
confidence: 72%
“…The time history of tip surface temperature on the middle blade tip in the cascade is recorded by a FLIR A325 IR camera, which has a spatial resolution of 320 � 240 and a sampling frequency of 60 Hz. The tip heat transfer coefficient is obtained by solving the heat conduction equation and Newton's law of cooling, as the same method in Ma et al 19 and Jiang et al 27 The uncertainty of the experimental result is acceptable on the whole tip surface, as is shown in Figure 5.…”
Section: Experimental Validationmentioning
confidence: 99%
“…It should be noted that the results of Wheeler's numerical work [26] showed that the cooling injection still has the potential to reduce overtip leakage losses. In the meantime, the results of Ma's experimental work [27] indicated that when the cooling injection is introduced, distinctive series of stripes in surface heat transfer coefficient are observed with an opposite trend in the chordwise variations on the squealer cavity floor and on the suction surface rim.…”
Section: Introductionmentioning
confidence: 92%